LANDSLIDE DISASTER MITIGATION BASED ON DISASTER RISK LEVEL IN GRESIK, EAST JAVA - Hadi, Shofwan; Hargono, Arief; Saputra, Hijrah (Universitas Airlangga, 2024)
Landslides are a natural disaster with a serious threat in Indonesia, especially in areas with vulnerable geographic conditions. Gresik Regency, East Java, is one such area that is prone to landslides. This research aims to identify mitigation measures that are appropriate to the level of landslide risk in Gresik Regency. The research method used is a descriptive approach by collecting secondary data from various reports and available data. The research results show that the proposed solution is to install an internet-based landslide Early Warning System (EWS) in locations that are prone to ground movement and landslides. This EWS is based on standard disaster risk assessment parameters, such as slope slope, slope direction, rock type, etc., which are adapted to regional conditions in Gresik Regency. Installation of this internet-based EWS has several innovative values, including providing added value for the organization and stakeholders, innovation in technology, can be replicated, can be applied sustainably, is in line with organizational values, and provides benefits to the organization. Short, medium and long-term activity stages are outlined to achieve successful implementation, including installing EWS, developing the latest formats and applications, as well as monitoring and outreach. The installation of an internet-based landslide EWS in Gresik Regency is an innovative step that has great potential to increase preparedness and reduce the impact of landslides. This EWS is in line with the values ​​of BPBD Gresik Regency and can be replicated by other agencies. Successful implementation depends on short, medium and long term planning steps, as well as ongoing efforts in system development and outreach to the community. It is hoped that this research can contribute to reducing the impact of landslides in Gresik Regency and similar areas in the future.